Effect of Bacterial Resistance of Escherichia coli From Swine in Large-Scale Pig Farms in Beijing - Liu, Xiaoxia; Liu, Qian; Cheng, Yongyou; Liu, Rui; Zhao, Ruting; Wang, Jishi; Wang, Yanyun; Yang, Shuming; Chen, Ailiang (Frontiers in Microbiology, 2022)
With the widespread using of antibiotics in the aquaculture industry, the issue of bacterial resistance has attracted more and more attention. The continuous emergence of multi-resistant bacteria has greatly threatened human and animal health and the quality and safety of livestock products. To control bacterial resistance, we should understand the effect of bacterial resistance. The purpose of this experiment was to explore the factors influencing the Escherichia coli (E. coli) drug resistance in large-scale pig farms. In this experiment, 296 strains of E. coli isolated and identified from large-scale pig farms in Beijing were used as the research objects. Drug sensitivity tests in vitro were used to determine the sensitivity of pig-derived E. coli to 10 antibiotics. SPSS logistic regression was employed to analyze the effects of seasons, pig types, sampling points (medication types) and sampling locations on resistance and multi-drug resistance of E. coli from pigs. The degrees of drug resistance of the 296 strains of pig-derived E. coli to 10 antibiotics were varied, their resistance rates were between 4.05% and 97.64%, and their multi-drug resistance was appalling, with the highest resistance to 6 antibiotics being 26.35%. The isolated strains were proved more resistant to tetracyclines, penicillin and chloramphenicol, which are commonly used for disease prevention in pig farms, and less resistant to quinolones and aminoglycosides, which are not used in pig farms. The resistance of the isolated strains in spring and summer was generally higher than that in winter. E. coli resistance in piglets, fattening pigs and sows was more serious than that in nursery and sick pigs. The results showed that the season, type of medication and type of pig had an effect on the pig-derived E. coli resistance, and the type of medication was the main factor influencing the pig-derived E. coli resistance.